The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2008
DOI: 10.1104/pp.108.128256
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Key Amino Acids and UDP-Sugar Donor Specificity of a Plant Glucuronosyltransferase, UGT94B1: Molecular Modeling Substantiated by Site-Specific Mutagenesis and Biochemical Analyses

Abstract: The plant UDP-dependent glucosyltransferase (UGT) BpUGT94B1 catalyzes the synthesis of a glucuronosylated cyanidinderived flavonoid in red daisy (Bellis perennis). The functional properties of BpUGT94B1 were investigated using protein modeling, site-directed mutagenesis, and analysis of the substrate specificity of isolated wild-type and mutated forms of BpUGT94B1. A single unique arginine residue (R25) positioned outside the conserved plant secondary product glycosyltransferase region was identified as crucia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
70
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(73 citation statements)
references
References 54 publications
(119 reference statements)
1
70
0
Order By: Relevance
“…This conclusion corroborates the recent hypothesis that an Arg residue proximal to the carboxylate of UDP-GA is the biochemical basis of GATs of both plant and animal origin (Noguchi et al, 2009a). Arg-140 does not correspond to Arg-25 of Bp UGAT (UGT94B1) (Osmani et al, 2008) or Arg-350 of Pf F7GAT (UGT88D7) (Noguchi et al, 2009a) in primary structure, providing another example of convergent evolution of plant GATs. This illustrates the positional plasticity of the crucial Arg residue in acquiring specificity for UDP-GA in UGT catalysis (see Supplemental Figure 2 …”
Section: Specificity Determinant Of Vv Gt5 For Udp-gasupporting
confidence: 74%
See 1 more Smart Citation
“…This conclusion corroborates the recent hypothesis that an Arg residue proximal to the carboxylate of UDP-GA is the biochemical basis of GATs of both plant and animal origin (Noguchi et al, 2009a). Arg-140 does not correspond to Arg-25 of Bp UGAT (UGT94B1) (Osmani et al, 2008) or Arg-350 of Pf F7GAT (UGT88D7) (Noguchi et al, 2009a) in primary structure, providing another example of convergent evolution of plant GATs. This illustrates the positional plasticity of the crucial Arg residue in acquiring specificity for UDP-GA in UGT catalysis (see Supplemental Figure 2 …”
Section: Specificity Determinant Of Vv Gt5 For Udp-gasupporting
confidence: 74%
“…Previous studies of two GATs, Bp UGAT (UGT94B1) of the red daisy flower (Bellis perennis) (Sawada et al, 2005;Osmani et al, 2008) and Pf F7GAT (UGT88D7) of Perilla frutescens (Noguchi et al, 2009a), showed that Arg-25 in Bp UGAT and Arg-350 in Pf F7GAT play an important role in recognition of UDP-GA. These results suggest plasticity of the mechanisms that alter the sugar donor specificity of UGTs.…”
Section: Identification Of a Residue That Critically Determines The Smentioning
confidence: 99%
“…Residues that confer UDP-GlcUA specificity have been examined using site-directed mutagenesis and protein modeling of BpUGT94B1, a UGT from red daisy (Bellis perennis) that conjugates glucuronic acid to flavonoids. This analysis identified an arginine outside of the signature sequence (Arg-25) as crucial for activity with UDP-GlcUA, with Arg-25 mutants exhibiting dramatically reduced activity with UDP-GlcUA and 3-fold increased activity with UDP-Glc (28). A conserved arginine is found in the corresponding position relative to the mature N terminus of all human UGTs of the UGT1 and UGT2 families.…”
Section: Discussionmentioning
confidence: 99%
“…The sugar donor specificity of UGTs is dictated by a small number of amino acid residues (Osmani et al, 2008;Noguchi et al, 2009;Ono et al, 2010a). The residues are located in three distinct domains: N-terminal, middle, and C-terminal (PSPG box) domains (Sayama et al, 2012).…”
Section: Homology Modeling and Mutagenesis Analysis Of Csgt2mentioning
confidence: 99%